ANTIMELODY, FIELD RECORDING, GERAKAN MUSIK EKSPERIMENTAL, DAN HANTU BARU YANG MENOLAK HANTU LAMA HAUNTOLOGY - Setyawan, Aris (UI Scholars Hub, 2025)
This article challenges the traditional definition of music, limited to seven fixed elements: melody, harmony, rhythm, pitch, tempo, dynamics, and texture. The author suggests that all sound can be considered 'sound art,' blurring lines between music and other auditory experiences. In Mark Fisher’s hauntology, modern music is depicted as stagnant, trapped in a neoliberal pastiche that cancels the future by repeating past styles without innovation. However, this article highlights alternatives through experimental music, such as the album ANTIMELODY (2024), which uses field recording to present raw environmental sounds, challenging conventional musical structures. Movements like Jogja Noise Bombing and experimental music group Senyawa explore noise-based sounds, rejecting traditional melodies and industrial nostalgia. Music distribution via Bandcamp or Senyawa’s decentralized approach challenges Spotify’s dominance, known for unfair royalty systems, by offering better artist compensation. This article argues that in the independent music scene, innovative alternatives persist, counteracting Fisher’s “cancellation of the future,” proving that new creativity can defy the haunting influence of past cultural forms.